Meningkatkan Kepuasan Pelanggan Trailfinders: Peran Kinerja Tour Guide dan Perceived Value di PT EXO Travel Indonesia - Yustina Klara; Made Darmiati; Teguh Hadisukarno (J-TRUE: Journal of Travel and Leisure, 2024)
This research was motivated by a decrease in the percentage of customers who used the services of PT EXO Travel Indonesia-Bali from 2020-2023, and there were customer complaints from agent Trailfinders regarding the tour guide’s performance, which impacted customer satisfaction. Tour guide performance is one of the important components of a travel company that affects customer satisfaction. The perceived value has the potential to be mediated in this research model. Therefore, this research aims to determine the influence of tour guide performance on customer satisfaction mediated by customer perceived value. The research method used is quantitative descriptive with collecting respondent data by distributing questionnaires to Trailfinders customers who have used EXO Travel Indonesia-Bali tour guide services and obtained 227 valid samples. Samples were taken using nonprobability sampling-purposive sampling techniques. The results of the respondents' data were analyzed using SmartPLS 4 software and the Partial Least Square Structural Equation Model (SEM-PLS) technique. The study's results explore that the direct performance of tour guides positively and significantly affects customer satisfaction and perceived value. The customer's perceived value directly affects customer satisfaction, and indirectly, the tour guide's performance positively and significantly affects customer satisfaction through the customer's perceived value as a mediator